The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1080/03014467600001781
|View full text |Cite
|
Sign up to set email alerts
|

Height, weight and menarche in Swedish urban school children in relation to socio-economic and regional factors

Abstract: During the period 1964-1973, a defined sample of 740 Swedish urban school children (360 girls and 380 boys) from 40 different urban areas all over the country were followed longitudinally. Height and weight were measured twice a year and age at menarche was recorded. Mean ages at peak height velocity (PHV) and peak weight velocity (PWV) were 11-91 years (SD 0-95) and 12-50 years (SD 1-08) for girls with average values of 8-30 cm/year (SD 1-32) and 7-37 kg/year (SD 1-94). Mean age at menarche was 13-05 years (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
2
4

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(76 citation statements)
references
References 16 publications
8
62
2
4
Order By: Relevance
“…It can be concluded that in this case a phenomenon, also noticed in other studies, of the long-term changes is happening faster in populations that had worse development conditions in the past [17,19,31,32,34,35,36,37,38,39,41].…”
Section: Discussion Summarymentioning
confidence: 67%
See 3 more Smart Citations
“…It can be concluded that in this case a phenomenon, also noticed in other studies, of the long-term changes is happening faster in populations that had worse development conditions in the past [17,19,31,32,34,35,36,37,38,39,41].…”
Section: Discussion Summarymentioning
confidence: 67%
“…Based on the results of this study's research and avoiding the hard-to-explain reasons of the observed phenomenon, it needs to be concluded that similar tendencies for the stabilization of body height level or even its retardation were noticed in works mentioned in the Introduction [2,9,11,15,16,17,18,19]. It has to be noticed, though, that in this study's research such phenomenon occurred only in the group of children living in the big city.…”
Section: Discussion Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, rapid growth in early childhood increases the risk of diabetes (56), possibly by increasing the work-load on ␤-cells, and children grow considerably faster than they did a century ago. In 1970, Swedish boys were (depending on social class) 14.5-16.8 cm taller by age 15 years than in 1883 (57). Early growth velocity and obesity may however be more important than final attained height in predisposing to diabetes (56).…”
Section: Discussionmentioning
confidence: 99%